Learning together: A case study of a partnership to co-create assessment criteria - Smith, Susan; Akhyani, Kimiya; Axson, Dan; Arnautu, Andre; Stanimirova, Ilina (International Journal for Students as Partners, 2021)
This case study outlines a staff-student partnership to co-create generic assessment criteria to use in a UK business school. It highlights the potential for staff-student partnerships to create a temporary subfield, in which the established power differentials of academia are dissolved and partnership values can be established. We draw on a series of 10 semi-structured interviews with partnership participants. The values that underpin partnerships are linked to three major phases of the partnership process: establishing the partnership, partnership operation and atmosphere, and the partnership outcomes. The findings indicate that the values of authenticity, reciprocity, and inclusion are critical antecedents to establishing a successful partnership and that careful attention should be paid to establishing the partnership. The case extends our understanding of the partnership process by emphasising these antecedents. The study is multi-authored, which reflects an extension to the partnership process described in the case study.